2019
DOI: 10.1016/j.neunet.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Putting a bug in ML: The moth olfactory network learns to read MNIST

Abstract: We seek to (i) characterize the learning architectures exploited in biological neural networks for training on very few samples, and (ii) port these algorithmic structures to a machine learning context. The Moth Olfactory Network is among the simplest biological neural systems that can learn, and its architecture includes key structural elements and mechanisms widespread in biological neural nets, such as cascaded networks, competitive inhibition, high intrinsic noise, sparsity, reward mechanisms, and Hebbian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…The ability of insects to quickly form associative memories after three to five trials has been demonstrated experimentally (47). However, in general, fewshot learning remains a difficult task for computational models, including insect-inspired models (62). We find that, when compared with learning-dynamics data of real insects (47), our model is able to show realistic learning dynamics that matches with the experimental observations.…”
Section: Odor-background Segregation: a Joint Effect Of Temporal And supporting
confidence: 59%
“…The ability of insects to quickly form associative memories after three to five trials has been demonstrated experimentally (47). However, in general, fewshot learning remains a difficult task for computational models, including insect-inspired models (62). We find that, when compared with learning-dynamics data of real insects (47), our model is able to show realistic learning dynamics that matches with the experimental observations.…”
Section: Odor-background Segregation: a Joint Effect Of Temporal And supporting
confidence: 59%
“…The ability of insects to quickly form associative memories after 3-5 trials has been demonstrated experimentally (44). However, in general fewshot learning remains a difficult task for computational models including insect inspired models (54). We find that, when compared with learning dynamics data of real insects (44) our model is able to show realistic learning dynamics that matches with the experimental observations.…”
Section: Discussionsupporting
confidence: 58%
“…Models of olfactory bulb and piriform cortical activity have been applied to analyze chemosensor array data (Raman and Gutierrez-Osuna, 2005; Raman et al, 2006). Algorithms based on the insect olfactory system have been employed to learn and identify odor-like inputs (Diamond et al, 2016; Delahunt et al, 2018) as well as to identify handwritten digits—visual inputs incorporating additional low-dimensional structure (Huerta and Nowotny, 2009; Delahunt and Kutz, 2018; Diamond et al, 2019). More broadly, insect mushroom bodies in particular have been deeply studied in terms of both their pattern separation and associative learning capacities (Hige, 2018; Cayco-Gajic and Silver, 2019).…”
Section: Discussionmentioning
confidence: 99%